Kappa-carrageenan as stabilizer for peanut butter - Farolan, Colleen Francesca Guinto (2000)
ABSTRACT Kappa-carrageenan was used as a stabilizer for peanut butter. The effects of roasting time (40, 50 and 60 minutes), level of stabilizer (0, 0.5 and 1%) and conditioning treatment on oil separation of peanut butter for a storage period of three months were studied. The results did not show any single treatment as being the most effective in stabilizing peanut butter using kappa-carrageenan as stabilizer. Statistical analysis revealed that there were no significant effects of the various roasting times, level of kappa-carrageenan nd conditioning treatment on the extent of oil separation. Only at a 1% level of stabilizer did the roasting time exert a significant effect on conditioned peanut butter. hence, at the given levels of Kappa-carrageenan added, oil separation cannot be prevented. Further studies have to be made on the effect of levels of kappa-carrageenan greater than 1% on the extent of oil separation in peanut butter.